0
$\begingroup$

For $x\in (-\pi, \pi) $, I want to know whether the following series following series are uniformly convergent on $(-\pi,\pi) $:
1. $\sum _{n=1}^{\infty}{(\frac {x}{n})^n} $
2. $\sum_{n=1}^{\infty}{\frac {1}{((x+\pi)n)^2}}$.
I think series in 2 has to be uniformly convergent for,
$|\frac{1}{((x+\pi)n)^2}|$ $\leq $ $\frac {1}{n^2} $ and as $\sum {\frac {1}{n^2}} $ is convergent, by Wierstrass M-test the series in (2) is uniformly convergent.
But I don't how to proceed for the series in (1). Any help please! Also tell if my answer to the (2)nd is correct.

$\endgroup$
  • 1
    $\begingroup$ I don't think your argument for (2) is right: as $x\to -\pi$ the expression blows up and is not less than $1/n^2.$ $\endgroup$ – spaceisdarkgreen Nov 24 '17 at 4:44
  • $\begingroup$ Thank you for pointing it out! $\endgroup$ – shwetha Nov 24 '17 at 5:01
1
$\begingroup$

For part (1) you have $$ \left|\frac{x}{n}\right|^n< \left|\frac{\pi}{n}\right|^n$$ and $$\sum_{n=1}^\infty \left|\frac{\pi}{n}\right|^n$$ converges so the M-test applies here.

Part (2) is funny, cause it seems pretty benign: $$ \sum_{n=1}^\infty \frac{1}{((x+\pi)n)^2} = \frac{1}{(x+\pi)^2}\sum_{n=1}^\infty \frac{1}{n^2} = \frac{\pi^2}{6(x+\pi)}$$ and yet it doesn't uniformly converge since whatever small difference remains from the nicely converging $\sum \frac{1}{n^2}$ is blown up arbitrarily large by the divergence as $x\to -\pi$ (as user284331 shows in detail in their answer).

$\endgroup$
  • $\begingroup$ But how do you say the series $\sum_{n=1}^{\infty}{(\frac {\pi}{n})^n} $ converges? $\endgroup$ – shwetha Nov 24 '17 at 5:00
  • $\begingroup$ @shwetha ratio test, or once $n>\pi$ compare with a geometric series. $\endgroup$ – spaceisdarkgreen Nov 24 '17 at 5:02
1
$\begingroup$

Number two is not correct: Let $S_{n}(x)=\displaystyle\sum_{k=1}^{n}\dfrac{1}{(x+\pi)^{2}}\dfrac{1}{k^{2}}=\dfrac{1}{(x+\pi)^{2}}\displaystyle \sum_{k=1}^{n}\dfrac{1}{k^{2}}$, $S(x)=\displaystyle\sum_{k=1}^{\infty}\dfrac{1}{(x+\pi)^{2}}\dfrac{1}{k^{2}}=\dfrac{1}{(x+\pi)^{2}}\displaystyle \sum_{k=1}^{\infty}\dfrac{1}{k^{2}}$, then $|S_{n}(x)-S(x)|=\dfrac{1}{(x+\pi)^{2}}\displaystyle \sum_{k\geq n+1}\dfrac{1}{k^{2}}$, if it were uniformly convergent, then for some $N$, we have $|S_{n}(x)-S(x)|<1$ for all $n\geq N$ and $x\in(-\pi,\pi)$, then fix the $n$, take $x\rightarrow-\pi^{+}$ and the expression blows up.

Compliment to @spaceisdarkgreen answer: $\left|\dfrac{\pi}{n}\right|^{n}\leq\left(\dfrac{n^{1/2}}{n}\right)^{n}=\dfrac{1}{n^{n/2}}\leq\dfrac{1}{n^{2}}$ for large $n$, so the series converges.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.